Sustained agreement rates in the longitudinal assessment of lupus patients to a Broad Consent for personal data and specimen usage in the RHINEVIT biobank - Richter, Jutta G.; Filla, Tim; Acar, Hasan; Bleck, Ellen; Kernder, Anna; Düsing, Christina; Vordenbäumen, Stefan; Schröder, Markus; Hansen, Ralf; Distler, Jörg H. W.; Schneider, Matthias (Frontiers in Medicine, 2023)
Background: Biobanks are essential structures for scientific research. The RHINEVIT biobank is used to recruit biomaterials from rheumatology patients in outpatient care and to conduct clinical research studies (e.g., cohort studies) and basic research. RHINEVIT established Broad Consents (BC) to allow extensive and pertained usage of data and biospecimen without the need for specific project restriction. For quality assurance aspects we compared the consent rate of individual items of the BC versions in patients with systemic lupus erythematosus (SLE) in the longitudinal. Methods: BCs were used for biomaterial donation. Informed consent data from RHINEVIT were analysed. Due to contents restructuring of the BC items due to changes from the templates of the working group of the Medical Ethics Commissions in the Federal Republic of Germany and GDPR requirements, content mapping of the items was performed for the analysis. Results: From 09/2015 to 03/2022 291 SLE outpatients donated biomaterials. In 119 patients, the BC was renewed at least once in a subsequent biomaterial donation. Three biomaterial donations were obtained in 21 patients and four in six patients using the respective BC. Only one consent was revoked. Consent to the BC topics showed consistently high rates of agreement (range 97.5-100%), with only some patients disagreeing with individual topics. This remained stable over time (median 526 days [Q1 400, Q3 844]). None of the patients disagreed with a certain topic in two consecutive visits. Conclusion: Modifications of the BC did not result in any relevant changes in the approval rates for SLE patients. RHINEVIT’s BC is successfully used for the quality-assured handling of excellently annotated biomaterial. The long-term use of the very valuable biospecimens for unrestricted research - also in an international context - continues to be guaranteed.